The Impact of Procedurally-Just Policing on Citizen Perceptions of Police During Traffic Stops: the Adana Randomized Controlled Trial - Sahin, Nusret (Journal of quantitative criminology, 2017)
Objectives: The process-based model of police legitimacy suggests, when police are perceived to make fair decisions and treat people with respect, they will be viewed as legitimate authorities. A randomized controlled trial was used to test the impact of a procedural justice policing intervention, relative to routine police behavior, during traffic stops for excessive speeding in Adana, Turkey. Methods: Drivers stopped by traffic officers for speeding violations were randomly assigned to treatment and control groups. Subjects in the treatment group received the procedural justice policing intervention during traffic stops, while subjects in the control group experienced business-as-usual traffic stops. Treatment officer behavior was guided by a script that helped to ensure that key components of a procedurally-just encounter were delivered. After completion of the traffic stop, drivers were interviewed on the encounter and general perceptions of traffic police. Results: The experimental analyses show that the infusion of procedural justice principles into police traffic stops does improve citizens' perceptions of the specific encounter relative to routine police traffic stops. However, the procedural justice treatment did not generate a robust improvement in citizens' general perceptions of traffic officers. Conclusion: These results indicate it might be overly optimistic to suggest a single positive encounter can exert a strong influence on durable citizen perceptions of confidence and trust in the police. In addition to ensuring procedurally-just encounters, police executives and police makers should also pay attention to other relevant performance dimensions such as crime control effectiveness, distributive fairness, and lawfulness to change global perceptions of the police.